Utilization of Gerontechnology Smart Pill Boxes Combination of Color and Sound to Improve Compliance in Taking Medication in The Elderly: a Review - Madury, Shalahuddin Al Madury (Journal of health research and technology, 2025)
Physiological changes in the elderly result in changes in the pharmacokinetics and pharmacodynamics of drugs in geriatric patients, requiring the use of several drugs taken simultaneously, this is called polypharmacy. Therefore, there is a potential for inappropriate drug use and a 2- to 3-fold increased risk of unwanted drug reactions (ADR) in this age group. A safe medication system needs to be developed and maintained to ensure that patients receive good medication care. Pillbox is a tool that serves to put medicine in place with the hope that long-term medication adherence can be met in elderly patients, so the use of pillboxes will be more useful to improve medication adherence to patients. Developing the innovation “MARI: smart pillbox” by combining color and sound can facilitate and help remind patients to take medicine, monitor treatment, and send compliance reports to Health services to be an excellent alternative that can be applied to elderly patients to improve medication compliance and avoid medication errors in elderly patient.